MICROSPORUM CANIS RINGWORM EPIDEMIC IN TEHRAN - M.Emami; M.Moghadami (Tehran University of Medical Sciences, 1982)
Twenty Patients, a family, their neighbors, and friends; with lesions suspicious of Ringworm infection, were referred to us within a period of 80 days. The Source of infection was found to be 3 persian Cats (a mother and two kittens) living with the family. The cats had multiple lesions around their nose and on abdomen which reveales the Prevalence of cutaneous fungi both on direct microscopic examination and culture. Sixteen of the 20 pateints examined 80% were positive both in Microscopic examination and culture. The rest were negative because they have used topical and systemic antifungal drugs. Of these positives 12(75%) had Tinea corporis and 4(25%) had Tinea capitis. The ege range of the patients with Tinea corporis was 2-9 years and for those with Tinea corpois was 5- 48 years. The causative agent in this epidemic was Microsporum canis which was most probably transmitted from the cats to this family, their friends and neighbors.